Kebijakan Indonesia dalam Menangani Krisis Kemanusiaan Pengungsi Rohingya dan Melindungi Keamanan Nasional - Priesdiantoro, Rasid; Azhari, Yulian; Santoso, Puguh; Widodo, Pujo; Sukendro, Achmed (CV. AFDIFAL MAJU BERKAH, 2024)
The Rohingya crisis has garnered global attention due to its wide-ranging humanitarian and security impacts. Indonesia, as a country committed to humanitarian principles and national security, has been involved in addressing this crisis. This study analyzes Indonesia's policy in handling the Rohingya crisis, with a focus on efforts to strengthen national security while providing humanitarian assistance. Through a descriptive-analytical approach, the author investigates the steps taken by the Indonesian government, including diplomacy, coordination with international organizations such as UNHCR, and collaboration with neighboring countries within ASEAN. The research also depicts the challenges faced by Indonesia in addressing this crisis, including the rejection of assistance from the Myanmar government and the complexity of Rohingya refugee repatriation. This analysis provides insights into Indonesia's role in resolving humanitarian crises and strengthening national security at regional and international levels.